2023
DOI: 10.1186/s41687-023-00544-4
|View full text |Cite
|
Sign up to set email alerts
|

Patient and clinician-reported experiences of using electronic patient reported outcome measures (ePROMs) as part of routine cancer care

Abstract: Background Cancer and its treatment can have significant impacts on health status, quality of life and functioning of patients. Direct information from patients regarding these aspects can be collected via electronic platforms in the form of electronic Patient Reported Outcome Measures (ePROMs). Research has shown that the use of ePROMS in cancer care leads to improved communication, better symptom control, prolonged survival and a reduction in hospital admissions and emergency department atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Previously, clinicians have reported that they would find an ePROMs solution easy to use and useful [43], as seen in this study. In this study, clinicians expressed worries around additional time, workload, and challenges around data integration with existing IT systems, also seen previously [13,18,43,44]. Perceived benefits highlighted in this study, such as being able to identify specific symptoms, side effects, and supportive care needs of patients, have also been reported elsewhere [43].…”
Section: Comparison With Other Worksupporting
confidence: 56%
See 2 more Smart Citations
“…Previously, clinicians have reported that they would find an ePROMs solution easy to use and useful [43], as seen in this study. In this study, clinicians expressed worries around additional time, workload, and challenges around data integration with existing IT systems, also seen previously [13,18,43,44]. Perceived benefits highlighted in this study, such as being able to identify specific symptoms, side effects, and supportive care needs of patients, have also been reported elsewhere [43].…”
Section: Comparison With Other Worksupporting
confidence: 56%
“…First, clinicians reported that the dashboard would not necessarily improve the effectiveness or productivity of treatment decision-making, nor would it make their job easier, despite saying that the dashboard would help support or facilitate shared decision-making in stage 1. Similarly, in the literature, PROMs are generally seen as useful for clinical decision-making, although they may not always directly impact the decisions made [13,14,47]. Our findings indicate that clinicians may possibly see PROMs as supporting decisions already being made, as opposed to changing the course of decisions entirely.…”
Section: Comparison With Other Workmentioning
confidence: 50%
See 1 more Smart Citation
“…At the time of writing this paper, it has enrolled over ten thousand patients with more than thirty-five thousand completed electronic questionnaires featuring the direct lay translation of CTCAE. Both patients and clinicians have responded positively to this service due to its benefits in enhancing care ( 39 ).…”
Section: Discussionmentioning
confidence: 99%